Exosomes derived from HCC cells induce sorafenib resistance in hepatocellular carcinoma both in vivo and in vitro. Issue 1 (December 2016) - Qu, Zhen; Wu, Junhua; Wu, Junyi; Luo, Dongjun; Jiang, Chunping; Ding, Yitao
Abstract Background Exosomes are carriers of intercellular information and regulate the tumor microenvironment. They play an important role in drug resistance by transporting RNA molecules and proteins. However, their effects on sorafenib resistance in hepatocellular carcinoma (HCC) are not completely understood. Methods Exosomes were isolated from two invasive hepatoma cell lines (MHCC-97 L and MHCC-97H), and their roles in regulating sorafenib resistance in liver cancer cells as well as the underlying molecular mechanisms were determined. The exosomes were analyzed by TEM (transmission electron microscopy), DLS (dynamic light scattering) and Western blotting. Cell viability, cell death and the effects of exosomes on the HGF/c-Met/Akt signaling pathway in cancer cells were analyzed by MTT assays, FACS analysis and Western blotting, respectively. Moreover, the effects of exosomes on sorafenib resistance in vivo were investigated using a subcutaneous transplantation tumor model in athymic nude mice. Results Exosomes derived from HCC cells were of the expected size and expressed the exosomal markers CD9 and CD63. They induced sorafenib resistance in vitro by activating the HGF/c-Met/Akt signaling pathway and inhibiting sorafenib-induced apoptosis. They also induced sorafenib resistance in vivo by inhibiting sorafenib-induced apoptosis. Moreover, exosomes derived from highly invasive tumor cells had greater efficacy than that of exosomes derived from less invasive cells. Conclusions These data reveal the important role of HCC cell-derived exosomes in the drug resistance of liver cancer cells and demonstrate the intrinsic interaction between exosomes and their targeted tumor cells. This study suggests a new strategy for improving the effectiveness of sorafenib in treating HCC.